A 21.5 - Mingquan Bao (IEEE Journal of solid state circuits)
A balanced Colpitts voltage-controlled oscillator (VCO) is designed and fabricated in a commercially available 0.25-μm SiGe BiCMOS process. It has the characteristics of the push-push VCO, i.e., the VCO has simultaneously a differential output at a fundamental frequency of 21.5 GHz and a single-ended output at the second harmonic frequency of 43 GHz. A differential tuning technique is applied to reduce the phase noise. The measured phase noise at 1-MHz offset is -113 dBc/Hz at 21.5 GHz and -107 dBc/Hz at 43 GHz. The corresponding output power is about -6 and -17 dBm, respectively, with a 5% tuning range and a 130-mW dc power consumption.